Iodine immobilization by materials through sorption and redox-driven processes: A literature review - Moore, Robert C.; Pearce, Carolyn I.; Morad, Joseph W.; Chatterjee, Sayandev; Levitskaia, Tatiana G.; Asmussen, Robert M.; Lawter, Amanda R.; Neeway, James J.; Qafoku, Nikolla P.; Rigali, Mark J.; Saslow, Sarah A.; Szecsody, Jim E.; et al. (The Science of the total environment, 2020)
Radioiodine-129 (129I) in the subsurface is mobile and limited information is available on treatment technologies. Scientific literature was reviewed to compile information on materials that could potentially be used to immobilize 129I through sorption and redox-driven processes, with an emphasis on ex-situ processes. Candidate materials to immobilize 129I include iron minerals, sulfur-based materials, silver-based materials, bismuth-based materials, ion exchange resins, activated carbon, modified clays, and tailored materials (metal organic frameworks (MOFS), layered double hydroxides (LDHs) and aerogels). Where available, compiled information includes material performance in terms of (i) capacity for 129I uptake; (ii) long-term performance (i.e., solubility of a precipitated phase); (iii) technology maturity; (iv) cost; (v) available quantity; (vi) environmental impact; (vii) ability to emplace the technology for in situ use at the field-scale; and (viii) ex situ treatment (for media extracted from the subsurface or secondary waste streams). Because it can be difficult to compare materials due to differences in experimental conditions applied in the literature, materials will be selected for subsequent standardized batch loading tests. [Display omitted] •Iodine immobilization processes include precipitation, sorption or encapsulation.•Fe, Cu & Bi materials sorb iodine species & are useful for remediation.•Bi materials are readily available, inexpensive & insensitive to redox processes.•IX resins, activated carbon & organoclays are effective sorbants for I− but not IO3−.•MOFs, LDHs & aerogels require further investigation for iodine immobilization.